ARTIFICIAL INTELLIGENCE AND ITS ECONOMIC CHALLENGES IN EU COUNTRIES: IMPLICATION FOR THE REPUBLIC OF MOLDOVA - MAIA PISANIUC (Global Economic Observer, 2025)
This article aims to determine the future influence of AI on the Moldovan economy. The relevance of this research topic derives from the European Commission's decision to launch the European AI Strategy as early as 2018, with fundamental objectives related to the adoption of AI throughout the economy, in both the public and private sectors. The strategy also aims to prepare society for the transformations brought about by AI, and to oversee the functioning of an appropriate ethical and legal framework that responds to the EU's vision regarding technological values. Global projections also estimate that, by 2030, around 70% of businesses will use at least one artificial intelligence technology, such as computer vision, natural language processing, virtual assistants, automation/robotics and machine learning. It is estimated that this technology will generate an additional annual increase in global GDP of around 1.2%, with disruptive effects on countries, businesses and the labour market. This makes the topic of this research a global issue of high timelines. The research method is a comparative approach to the benefits of AI and the risks it may generate. Synthesis and inference, as well as scenario building based on factual data and a pragmatic approach that respects realism and the possibility of anticipating disruptive actions. The research will quantify the impact of AI on the structure of the Moldovan economy and the new business models it will generate, as well as the problems that may arise in connection with it. The research will also identify how the labour market of the Republic of Moldova will change in the context of EU integration and assess the current preparedness for the implementation of EU strategies in the field of AI.